Parallel SER analysis for combinational and sequential standard cell circuits. (April 2016) - Sheng, Weiguang; Jiang, Jianfei; Mao, Zhigang
Abstract: A parallel SER (soft error rate) evaluation framework ASSET-VLG was developed to analyze the SER of both combinational and sequential standard cell circuits. ASSET-VLG was constructed in practically oriented way: (i) it employs a verilog parser for automatically reading the synthesized DUT (device under test) netlist; (ii) it provides an accurate and unified SER analysis framework for both the combinational and sequential circuits rather than the former only; (iii) it targets to a 130 nm production library and the modeling method can be easily ported to newer technologies. Furthermore, concurrency is also exploited for accelerating the evaluation procedure on modern multi-core computers. These features make ASSET-VLG appropriate for automatic SER estimation in design stage and can be easily integrated into current highly reliable ICs design flow. Experiments on ISCAS׳85 and ISCAS׳89 benchmark circuits show the evaluation time ranges from 0.5 ms to 2.16 s without previous memory explosion problem. Compared with spice, the modeling method of ASSET-VLG provides 98% accuracy. The parallelizing experiments indicate the proposed method has better scalability, e.g., 4.44 X speedup are obtained in a 4 cores/8 threads platform. The experiments also reveal that sequential part (flip-flops) in the circuit dominating the system SER by one order than combinational gates for a 130 nm CMOS process. Last but not least, significant frequency dependence of SER are observed in flip-flops, implying the commonly used critical charge measure is insufficient for characterizing soft error in sequential cells.